A probabilistic-based framework for the integrated assessment of seismic and energy economic losses of buildings. (15th October 2022) - Bianchi, Simona; Ciurlanti, Jonathan; Overend, Mauro; Pampanin, Stefano
Highlight: Seismic safety and environmental sustainability need to be considered simultaneously. A probabilistic risk assessment is proposed to support building investment decisions. Integrated seismic and energy economic losses are used as design decision variable. Traditional vs low-damage seismic-resisting technologies are investigated. Design solutions are assessed and compared in terms of reliability and risk values. Abstract: Structural safety and environmental sustainability are major factors in investment decisions for building systems, but are rarely considered simultaneously. Recent research efforts have redressed this by developing assessment methodologies and technical solutions for integrated energy efficiency and seismic performance. These studies are typically limited to existing buildings and retrofit interventions at global building scale, whereas an effective framework could and should be part of the design process of either new or existing buildings at both building and component scales. This paper proposes a probabilistic-based assessment framework to assess the building performance in terms of integrated economic losses and support the selection of resilience-enhanced solutions. The proposed methodology is validated through its application to reinforced concrete case-study buildings consisting of traditional vs low-damage earthquake-resistant technologies coupled with energy efficiency strategies. Seismic and energy risk assessment analyses are performed accounting for both modelling uncertainties and earthquake/weather variability. Probabilistic distributions of the integrated economic losses are finally derived to compare the design solutions in terms of risk and reliability. The research outcomes demonstrate the effectiveness of the probabilistic approach for decision-making in building projects. Specifically, it is found that the economic losses can be highly underestimated (greater than40 %) in the single domains (energy or seismic); greater savings and return on investment can be achieved when the seismic safety is involved in the design process; probabilistic distributions and reliability/risk values can represent an effective tool to assess and compare design solutions.